1976
DOI: 10.1364/ao.15.003006
|View full text |Cite
|
Sign up to set email alerts
|

Recording the parallelism of optically contacted Fabry-Perots

Abstract: A simple device has been constructed to record accurately the parallelism of optically contacted Fabry-Perots immediately after their manufacture. In this a Fabry-Perot fringe is tuned to be a maximum on-axis by varying the pressure of the gas in which the etalon is emersed. An insect-eye lens is then used to photograph the different fringe patterns from a large number of separate small areas of the Fabry-Perot simultaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Our test is effective over the full range of TTF spacings down to 2 mm. Alternative techniques for measuring parallelism, such as beam partitioning by insect-eye lenses (Meaburn et al 1976), were explored and found impracticable for an astronomical imager such as TTF. A novel CCD charge-shuffling technique is employed that involves multiply exposing a single CCD image during the test.…”
Section: Introductionmentioning
confidence: 99%
“…Our test is effective over the full range of TTF spacings down to 2 mm. Alternative techniques for measuring parallelism, such as beam partitioning by insect-eye lenses (Meaburn et al 1976), were explored and found impracticable for an astronomical imager such as TTF. A novel CCD charge-shuffling technique is employed that involves multiply exposing a single CCD image during the test.…”
Section: Introductionmentioning
confidence: 99%